The analysis of competitive strategies from the perspective of small and medium enterprises - Pavlović, Nebojša; Čelić, Irena (Hotel and Tourism Management, 2020)
In contemporary conditions of the economy, the small and medium-sized enterprises (SME) face numerous challenges because of the constant changes, which create both new threats and opportunities. The competition is fierce in the market – only those with clear plans and strategies will manage successful businesses. The companies relying on no strategy or using a little bit of everything cannot be expected to thrive. The paper will explain in more depth the particularities and ways of organizing an entrepreneurship activity in the SMEs. Furthermore, it would describe competitive strategies and their positioning within an SME. The aim of this study is to explore competitive strategies and ways of their application in the SME.